Extracellular Vesicles Derived From Olfactory Ensheathing Cells Promote Peripheral Nerve Regeneration in Rats - Xia, Bing; Gao, Jianbo; Li, Shengyou; Huang, Liangliang; Ma, Teng; Zhao, Laihe; Yang, Yujie; Huang, Jinghui; Luo, Zhuojing (Frontiers in Cellular Neuroscience, 2019)
Accumulating evidence showed that extracellular vesicles (EVs) and their cargoes are important information mediators in nervous system and have been proposed to play an important role in regulating regeneration. Moreover, many studies reported that olfactory ensheathing cells (OECs) conditioned medium is capable of promoting nerve regeneration and functional recovery. However, the role of EVs derived from OECs in axonal regeneration has not been clear. Thereby, the present study was designed to firstly isolate EVs from OECs culture supernatants, and then investigated their role in enhancing axonal regeneration after sciatic nerve injury. In vitro studies showed that OECs-EVs promoted axonal growth of dorsal root ganglion, which is dose-dependent and relies on their integrity. In vivo studies further demonstrated that nerve conduit containing OECs-EVs significantly enhanced axonal regeneration, myelination of regenerated axons and neurologically functional recovery in rats with sciatic nerve injury. In conclusion, our results, for the first time, demonstrated that OECs-EVs are capable of promoting nerve regeneration and functional recovery after peripheral nerve injuries in rats.